MEDIASI KOMITMEN ORGANISASI: MENJEMBATANI KESENJANGAN ANTARA KETERIKATAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA SEKTOR PUBLIK - Sholichah, Naffa Atus; Mulyana, Olievia Prabandini (Penerbit Lafadz Jaya, 2025)
This study aims to investigate the relationship between work engagement and organizational citizenship behavior among government employees through organizational commitment as a mediating variable. The problem identified in this study is the low level of work engagement among some employees who admit to feeling bored with their work. In addition, employee citizenship behavior is not yet optimal, employees are less open to existing working conditions and facilities, communication between employees is still often not smooth, and cooperation is not yet consistent when colleagues are absent. The present study employs a quantitative approach, utilising purposive sampling of 114 employees with a minimum service duration of 1 year. The data were collected through the administration of an online questionnaire and subsequently analysed using SPSS with the PROCESS macro for mediation analysis. The findings indicate that organisational commitment serves as a complete mediator in the relationship between work engagement and organisational citizenship behaviour, as evidenced by an indirect effect size of 0.38 (95% CI [0.16, 0.75]). This finding suggests that work engagement alone is insufficient to generate organizational citizenship behavior; instead, strong emotional commitment to the organization is a necessary condition for translating work engagement into extra-role behavior in the public sector context.